A Comprehensive Systematic Review of Blood Pressure Variability during Mechanical Thrombectomy under Anesthesia - Nadya Larasati; Ashri Mirawati (The International Journal of Medical Science and Health Research, 2026)
Introduction: Mechanical thrombectomy (MT) is the standard of care for acute ischemic stroke due to large vessel occlusion. However, optimal blood pressure (BP) management during MT under anesthesia remains uncertain, particularly regarding blood pressure variability (BPV) and its impact on clinical outcomes. This systematic review comprehensively synthesizes evidence on BPV during MT under anesthesia. Methods: We systematically screened studies from multiple databases including adult patients (≥18 years) undergoing MT under any form of anesthesia, reporting intra-procedural BPV metrics with continuous BP monitoring. Study designs included randomized controlled trials, cohort studies, case-control studies, systematic reviews, and meta-analyses with sample sizes ≥5 patients in appropriate clinical settings. Data extraction encompassed study characteristics, patient populations, anesthesia management, BP measurement methods, BPV patterns, clinical outcomes, statistical associations, and predictive factors. Results: From 104 included sources, consistent patterns emerged despite substantial methodological heterogeneity. Observational studies demonstrate associations between intraoperative BP drops and worse functional outcomes (1,2), particularly when mean arterial pressure decreases exceed 20-40% from baseline (3). Randomized trials comparing general anesthesia with procedural sedation show mixed results, with three single-center trials demonstrating equivalence or modest benefit for general anesthesia when strict protocols are applied (6,7,19). Intensive BP lowering post-thrombectomy consistently demonstrates harm (9,10), with the ENCHANTED2/MT trial showing intensive targets <120 mmHg worsened outcomes (9). BPV metrics including standard deviation, coefficient of variation, and successive variation are associated with functional outcomes, though definitions vary widely (11,12). Critical gaps include underrepresentation of posterior circulation strokes, large core infarcts, and patients with extended time windows. Discussion: The evidence converges on avoiding profound hypotension during MT, with thresholds of MAP <70 mmHg for >10 minutes associated with poor outcomes (4). However, optimal absolute thresholds remain contested. The interaction between anesthesia technique and BP management introduces complexity, with dedicated neuroanesthesia teams and protocol-mandated targets potentially more important than anesthesia modality per se. Current BPV metrics fail to capture temporal dynamics and clinical context of pressure changes. Conclusion: BPV during MT under anesthesia is critically associated with clinical outcomes. Future research requires adequately powered multicenter trials with standardized BPV metrics, comparative effectiveness studies of vasoactive agents, and prospective registries including underrepresented populations. Individualized BP management strategies accounting for patient-specific factors remain inadequately tested.